PP.04.03: LEFT VENTRICULAR SYSTOLIC DYSFUNCTION AND CHRONIC KIDNEY DISEASE IN HYPERTENSIVE PATIENTS. (June 2015) - Tilea, I.; Tatar, C.M.; Tatar, R.; Voidazan, S.; Bocicor, E.A.; Xantus, T. Szakacs; Varga, A.
Abstract : Objective: Heart failure (HF) is a common feature in hypertensive patients, increasing the risk of mortality. Chronic kidney disease (CKD) is also known to be involved in the etiology of HF. However, among hypertensive patients the associations of different stages of CKD and changes in cardiac structure, respectively in left ventricular systolic function are not well described. A cross-sectional study was performed to evaluate the impact of different stages of CKD concerning left heart failure. Design and method: 79 hypertensive patients, mean age 64.09+/-10.05 years were evaluated. Left ventricle dimensions and ejection fraction (EF) were assessed by 2D echocardiography and CKD by determining estimated Glomerular Filtration Rate (eGFR) using MDRD formula. Subjects were divided in two subgroups (49 pts. – 62.03% with CKD hemodialysis naive and 30 pts. – 37.97% without CKD). Other variables: presence of diabetes mellitus, total cholesterol, triglycerides were also considered. Results: In hypertensive patients over 60 years of age CKD was diagnosed more frequently. The prevalence of left ventricular hypertrophy (LVH) assessed by echocardiography (35 patients of 79 total) was 0(0%), 11 (13.92%), 12 (15.19%), 6 (7.59%), 3 (3.8%), for eGFR categories over 90, 60–89, 45–59, 30–44, and <30 ml/ min per 1.73m2, respectively. Systolic dysfunction (defined as EF less than 45%) was present in 6.32% of the cohort. The majority of patients (78.49%) had an EF>50%; only 15.18% of patients had EF = 46%–50%, 6.32% of patients had 36%–45%, and none had EF less than 35%. There was no association between kidney function and systolic dysfunction in demographic, multivariate, or fully adjusted models. Average EF in CKD stages was 62% in stage 2, 61% in stage 3A/3B and 55% in stage 4, with no significant statistical difference with group without CKD (64%). Multivariate logistic regression applied did not outlined any statistical significance between the groups. Conclusions: Chronic Kidney Disease hypertensive patients have higher prevalence of left ventricular hypertrophy, which was more pronounced in CKD stage 2–3. In our study, we did not detect significant associations between different stages of CKD and decreased ejection fraction after adjusting for potential confounding variables in hypertensive patients.